Ethnoscience-Based Instructional Materials for Natural and Social Sciences in Elementary Schools: A Bibliometric Analysis - Setiyadi, Desi (EduBase : Journal of Basic Education, 2025)
Research on ethnoscience-based instructional materials in Natural and Social Sciences (IPAS) education has grown in recent years. However, a significant gap remains in bibliometric analysis and systematic mapping, limiting the understanding of research trends, collaboration patterns, and key themes in this field. Objective: This study aims to conduct a bibliometric analysis of ethnoscience-based IPAS instructional materials to identify publication trends, researcher networks, and thematic focuses. Novelty: Unlike previous studies focusing on classroom implementation, this research offers the first bibliometric mapping of ethnoscience in IPAS materials. Methods: This study used a systematic literature review and bibliometric analysis of Scopus-indexed publications (2020–2025). Data was analyzed using VOSviewer 1.6.20, Biblioshiny, and Microsoft Excel to identify trends and key research themes. Results: The findings reveal that Indonesia and China are the top contributors, with dominant themes including curriculum development and student engagement. Research collaboration remains limited, with only 16.73% of studies involving international partnerships. Additionally, challenges include the lack of a standardized framework for implementing ethnoscience in elementary curricula. Conclusion: This study highlights the need for cross-disciplinary collaboration between educators, researchers, and policymakers to enhance the application of ethnoscience in elementary school. Strengthening international partnerships will further support the development of culturally responsive and scientifically robust instructional materials.